In silico Screening of Zinc Database for Discovery of Novel Urease Inhibitors as a Remedy to Gastro-Duodenal Ulcer Caused by Helicobacter pylori (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Design and synthesis of novel urease inhibitors taking center stage now days with specific attention as a remedy to Helicobacter pylori infection. A number of inhibitors fail in vivo and in clinical trial owing to the toxicity and hydrolytic profile. In the present study, we are making an attempt to screen a large small molecule database, ZINC, for a potential urease inhibitor. The structure based drug discovery approach has been adopted with acceptable ADMET parameters so that the lead molecules may have fair chances of passing in vitro and in vivo trails. The lead molecule in our study, with ID ZINC90446454 is a urea derivative and predicted to be nontoxic. It comes out to be a promising drug candidate with pKd value 7.83, LE 0.429 and LD50 value 10100 mg/kg body weight. Its sulfanyl derivative, with predicted high LD50 (10100 mg/kg body weight), exhibits the feasibility of a disulfide covalent bond with Cys321 in the active site. The derivative may serve as a novel covalent inhibitor with high specificity, high potency and low toxicity. The derivative, in future, may be a successful drug candidate for H. pylori induced gastro-duodenal ulcer.